Evaluation of a robust engineered enzyme towards organophosphorus insecticide bioremediation using planarians as biosensors. (1st June 2019) - Poirier, Laetitia; Pinault, Lucile; Armstrong, Nicholas; Ghigo, Eric; Daudé, David; Chabrière, Eric
Abstract: Organophosphorus compounds (OPs) are neurotoxic molecules developed as insecticides and chemical warfare nerve agents (CWNAs). They are covalent inhibitors of acetylcholinesterase (AChE), a key enzyme in central and peripheral nervous systems and are responsible for numerous poisonings worldwide. Many animal models have been studied over the years but finding a suitable in vivo model to account for both acute toxicity and long-term exposure remains a topical issue. Recently, an emerging aquatic animal model harboring a mammalian-like cholinergic nervous system, the freshwater planarian from Platyhelminthes, has been used to investigate neurotoxicity and developmental disruption. Given the tremendous toxicity of OPs, various bioremediation strategies have been considered over the years to counter their poisonous effects. Among these, enzymes have been particularly highlighted as they can degrade OPs in a fast, non toxic and environmentally friendly manner. In this article we investigated the biotechnological potential for decontaminating OPs of the previously reported variant Sso Pox-αsD6 from the hyperstable enzyme Sso Pox, isolated from the archaea Sulfolobus solfataricus . The capacity to hydrolyze 4 new substrates (methyl-pirimiphos, quinalphos, triazophos and dibrom) was demonstrated and the degradation products generated by enzymatic hydrolysis were characterized. We further evaluated the capacity of Sso Pox-αsD6 for in vivo protection of freshwater planarians Schmidtea mediterranea ( Smed ). The use of Sso Pox-αsD6 drastically decreased mortality and enhanced mobility of planarians. Then, an enzyme-based filtration device was developed by immobilizing intact Escherichia coli cells expressing Sso Pox-αsD6 into alginate beads. The efficacy of the device was demonstrated using planarians as biosensors. Graphical abstract: Image 1 Highlights: Organophosphorus (OPs) are neurotoxic insecticides with acute and chronic toxicity. Enzymatic bioremediation is promising for limiting poisoning effects of OPs. SsoPox is a highly robust enzyme able to efficiently degrade OPs. SsoPox decreases mortality and behavioral disruption in planarians. An enzyme-based filtration device allows fast decontamination of soiled water.